2011 Seventh International Conference on Intelligent Sensors, Sensor Networks and Information Processing 2011
DOI: 10.1109/issnip.2011.6146616
|View full text |Cite
|
Sign up to set email alerts
|

Event reliability in Wireless Sensor Networks

Abstract: Ensuring reliable transport of data in resource constrained Wireless Sensor Networks (WSNs) is one of the primary concerns. The two reliability mechanisms typically used in WSNs are packet reliability and event reliability. Packet reliability requires all packets from all the sensor nodes to reach the sink that can result in wastage of sensors' limited energy resources. The sensing regions of densely deployed sensor nodes often overlap with one another and data from nodes that are in close proximity tend to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Mahmood et al [29], proposed Event Reliability Protocol (ERP), whose objective is to provide reliable delivery of information regarding event occurrence to the sink. Authors have proposed a spatio-temporal correlation mechanism to ensure that packets containing information about same event are not transmitted thus reducing traffic.…”
Section: Retransmission Based Event Detection Hop By Hop Reliabilitymentioning
confidence: 99%
“…Mahmood et al [29], proposed Event Reliability Protocol (ERP), whose objective is to provide reliable delivery of information regarding event occurrence to the sink. Authors have proposed a spatio-temporal correlation mechanism to ensure that packets containing information about same event are not transmitted thus reducing traffic.…”
Section: Retransmission Based Event Detection Hop By Hop Reliabilitymentioning
confidence: 99%
“…So the enumeration methods can be employed for networks of relatively small size and there is a need of faster computational procedures that can provide an accurate approximation of complex WSN. In [43] paper, the author present a hexagon tessellation sensor network model with role assignment scheme and estimate the reliability and lifetime distribution by employing a new improved Monte Carlo scheme which incorporates both simulation and analytic methods and is suitable for the WSN. Also it is shown that the node sub-roles and node density have important effects on the network reliability and lifetime.…”
Section: Classification Of Reliability Modeling and Evaluationmentioning
confidence: 99%
“…When the node hears that the next hop node transmitting the packet it has sent, it is an implicit acknowledgement that the packet is forwarded successfully [14]. And the node then removes the packet from the queue end and the next packet in the queue is processed.…”
Section: Erp (Event Reliability Protocol)mentioning
confidence: 99%